2013
DOI: 10.1002/ab.21520
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of marijuana use from adolescence to adulthood: Relationship with using weapons including guns

Abstract: This is the first study to assess the associations between the trajectories of marijuana use and other predictors of violent behavior with the use of guns or other weapons as well as stealing without the use of weapons among inner-city African Americans and Puerto Ricans (N=838). Logistic regression analyses examined whether the longitudinal trajectories of marijuana use compared with the trajectory of no/low marijuana use predicted violent behavior. A higher Bayesian posterior probability (BPP) for the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…For instance, the trajectories of chronic and increasing marijuana use may be associated with drug-prone personality attributes and psychiatric conditions, difficulties in interpersonal relations, and environmental factors, such as financial difficulty [1014]. In recent years, a number of investigators have attempted to identify the patterns or trajectories of marijuana use [3, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the trajectories of chronic and increasing marijuana use may be associated with drug-prone personality attributes and psychiatric conditions, difficulties in interpersonal relations, and environmental factors, such as financial difficulty [1014]. In recent years, a number of investigators have attempted to identify the patterns or trajectories of marijuana use [3, 15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Caldeira et al (2012) [3] reported that chronic and late-increasing marijuana users had the worst health outcomes, including functional impairment due to injury, illness, or emotion problems. In a sample of African American and Puerto Rican adolescents and adults, chronic marijuana use was associated with increased violence, greater financial instability, and increased sexual risk behavior [10, 16]. In a study using national panel data, Schulenberg and colleagues (2005) [13] reported that chronic marijuana use was related to a greater likelihood of marijuana dependence and substance abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Kelley's first on-record interaction with law enforcement authorities was when he was arrested for possession of marijuana and, subsequently, expelled from his high school. Since then, the record shows that Kelley started using marijuana frequently, as well as developing mental health issues that would lead him to have problems in his employment with the United States Air Force and multiple instances where he abused his step-son and his wife at the time [11,12].…”
Section: Marijuana Violencementioning
confidence: 99%
“…These are among the many nationally reported violent cases that have, among others factors, a common root to what led these young people to commit acts of violence at the detriment to society as a whole: the extensive use or abuse of marijuana. In recent years, many States within the United States, as well as some other countries around the world, have decriminalized or legalized the recreational use of marijuana [8,12,13,19].…”
Section: Marijuana Violencementioning
confidence: 99%
See 1 more Smart Citation